Antarctic waters (Area V) near the Balleny Islands are a summer feeding area for some eastern Australian Breeding Stock E(i) Humpback Whales (Megaptera novaeangliae) - Franklin, Wally; Franklin, Trish; Brooks, Lyndon; Gibbs, Nadine; Childerhouse, Simon; Smith, Franz; Burns, Daniel; Paton, David; Garrigue, Claire; Constantine, Rochelle; Poole, M. Michael; Hauser, Nan; et al. (J. Cetacean Res. Manage., 2023)
Discovery mark tagging provided the first evidence of linkages between eastern Australian and Oceania Humpback whale breeding grounds and the Antarctic Area V feeding areas. Early investigation of movements of humpback whales in the Western Pacific led to the view that the Balleny Islands and the Ross Sea were the summer destinations for humpback whales from eastern Australia and the Oceania breeding grounds. Recent photo-identification (ID) studies provided further evidence of low levels of migratory interchange and complex linkages within Oceania and between eastern Australia and Oceania. We report here the migratory movement of three humpback whales (Megaptera novaeangliae) between Eastern Australia (E(i) breeding stock) and the Area V Antarctic feeding area in the vicinity of the Balleny Islands. Using photo-ID techniques, comparisons between a Balleny Island fluke catalogue (n = 11 individuals) and existing fluke catalogues from eastern Australia (n = 3,120 individuals) and Oceania (n = 725 individuals), yielded three matches to Hervey Bay, Byron Bay and Ballina in eastern Australia and no matches to Oceania. The eastern Australia catalogue (n = 3,120) was made up of Hervey Bay (n = 1,556), Byron Bay, (n = 916) and Ballina (n = 648). The Oceania catalogue (n = 725) is made up of Tonga (n = 282); New Caledonia (n = 160); French Polynesia (n = 159); New Zealand (n = 41); Cook Islands (n = 36); American Samoa (n = 31); Vanuatu, Niue, Samoa and Fiji (n = 11) and Norfolk Island (n = 5). Only three previous individual photo-ID matches have been reported between eastern Australia Breeding Stock E(i) and Antarctic Area V feeding areas in the vicinity of the Balleny Islands and the Ross Sea. Only one genotype match has been reported between Antarctic Area V feeding areas and Oceania breeding grounds. An analysis of the frequencies of whales seen and not seen in the Balleny Islands, Oceania and eastern Australia, relative to the expected frequencies, based on the estimated population sizes and the sizes of the catalogues, supports the hypothesis that Antarctic Area V waters, in the vicinity of the Balleny islands, is a summer feeding area for some eastern Australian humpback whales.